Notice of some Unrecorded Sculptured Stones at Edderton, Ross-shire, and at Foss, Perthshire (Proceedings of the Society of Antiquaries of Scotland, 1911)
A slab at Edderton has an incised, equal-armed cross with trefoil ends, and, below it, a long sword with recurved guards, pointed trefoil pommel, and blunt point. In the fourth quadrant of the cross there is a lion rampant, langued. The stone has evidently been a palimpsest, used and lettered more than once, for initials of later occupants of the grave have been cut through part of the cross and the lion. The stone is probably originally of the thirteenth or fourteenth century. A lintel now in the billiard-room of Balnagown Castle, but formerly in the mansion-house of Daan, in the Parish of Edderton has three circles, each 16 inches in diameter, and at each end of the stone is a bearded human face carved inside a semicircle enclosed within a moulding. Between the middle circle and the others are the initials A and M and M and F. Just above the latter, and beginning after the crescent, is the motto " SOLI DEO GLO-RIA," with the date 1680. The first and third circular panels have coats of arms with mottoes. In the middle panel is a man in what appears to be a Geneva\r cloak, and with a small skull-cap on his head. He holds in his hands a book, whereon is written, " Fear God in hairt as ye may be bad." Surrounding the figure is the motto " SEEVIRE DEO EST REGNAEE," and the initials M H M E R. The third stone is a lintel in Edderton House, inscribed with initials at different dates and a text from Scripture. A standing stone with an incised cross on one face survives at Tombreck.